Rolf Stein's Tibetica antiqua : with additional materials - Stein, R. A. (Rolf Alfred), 1911-1999 (Brill's Tibetan studies library ;, 2010)
Tibetica antiqua represents the seminal work on Tibetan religious history by one of the foremost Tibetologists of the twentieth century. Herein, Stein discusses the cultural and religious interactions among Tibet, India, and China which resulted in what we now consider "Tibetan Buddhism" from the point of view of our earliest sources, the Dunhuang manuscripts. Stein first discusses the basic tool of religious language, and the extent to which translations from Chinese, often apocryphal, scriptures competed with translations from Sanskrit. Stein also analyzes evidence for the introduc.